Ketentuan Hukum Positif Indonesia Dalam Mengatur Perkawinan Beda Agama dan Akibat Hukumnya - Megawati Megawati (JOURNAL of LEGAL RESEARCH, 2022)
Compilation of Islamic Law discussion of interfaith marriage is regulated in the chapter on marriage prohibition which is described in articles 40 to 44. This study aims to determine the provisions of positive Indonesian law in regulating interfaith marriages. In addition to knowing the law of interfaith marriage according to positive Indonesian law. This study uses a qualitative research method with a statutory approach. The results of the study stated that there were negative consequences of interfaith marriages, both from the psychological and juridical aspects. The psychological aspect is indicated by the waning and not achieving the goals of domestic life. This interfaith marriage slowly destroys the happiness in the household. In addition to fighting over the influence of children to follow the teachings of their respective religions which causes children to be mentally disturbed.